Interlaboratory validation of cerebrospinal fluid α‐synuclein quantification in the diagnosis of sporadic Creutzfeldt‐Jakob disease. Issue 1 (6th July 2018) - Kruse, Niels; Heslegrave, Amanda; Gupta, Vandana; Foiani, Martha; Villar‐Piqué, Anna; Schmitz, Matthias; Lehmann, Sylvain; Teunissen, Charlotte; Blennow, Kaj; Zetterberg, Henrik; Mollenhauer, Brit; Zerr, Inga; et al.
Abstract: Introduction: Cerebrospinal fluid α‐synuclein level is increased in sporadic Creutzfeldt‐Jakob disease cases. However, the clinical value of this biomarker remains to be established. In this study, we have addressed the clinical validation parameters and the interlaboratory reproducibility by using an electrochemiluminescent assay. Methods: Cerebrospinal fluid α‐synuclein was quantified in a total of 188 sporadic Creutzfeldt‐Jakob disease and non–Creutzfeldt‐Jakob‐disease cases to determine sensitivity and specificity values and lot‐to‐lot variability. Two round robin tests with 70 additional cases were performed in six independent laboratories. Results: A sensitivity of 93% and a specificity of 96% were achieved in discriminating sporadic Creutzfeldt‐Jakob disease. No differences were detected between lots. The mean interlaboratory coefficient of variation was 23%, and the intralaboratory coefficient of variations ranged 2.70%–11.39%. Overall, 97% of samples were correctly diagnosed. Discussion: The herein validated α‐synuclein assay is robust, accurate, and reproducible in identifying Creutzfeldt‐Jakob disease cases. Thus, it is ready for implementation in the clinical practice to support the diagnosis of Creutzfeldt‐Jakob disease. Highlights: A new cerebrospinal fluid α‐synuclein assay is validated for the diagnosis of sCJD. High diagnostic accuracy allows 97% of correct diagnoses. Two round robin tests unveil high interlaboratory reproducibility. Clinical parameters are superior to those of other established biomarkers.